PENGARUH GREEN ACCOUNTING, STRUKTUR MODAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Ruhiyat, Endang; Kurniawan, Muhammad Erick (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the influence of green accounting, capital structure and corporate social responsibility on financial performance with good corporate governance as a moderating variable. This type of research is quantitative research using secondary data. The population in this research is the index sector compass 100 companies listed on the Indonesia Stock Exchange in 2018-2022, totaling 100 companies. The sample determination in this research was carried out using a purposive sampling technique and a sample of 11 companies was obtained. The data analysis technique used is panel data regression analysis with the Eviews 12 application. Based on the research results, it can be concluded that it is partially green accounting and capital structure have an influence on financial performance, while corporate social responsibility has no influence on financial performance. Based on analysis through moderated regression analysis, good corporate governance is unable to moderate the influence of green accounting, capital structure and corporate social responsibility on financial performance, capital structure and corporate social responsibility terhadap kinerja keuangan